PENGARUH TEKNIK VIDEO EDUKASI TERHADAP RASA INSECURE PADA SISWA KELAS VIII TAHUN PELAJARAN 2022/2023 - Cindi Nurmawati; I Made Gunawan; Eneng Garnika (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
ABSTRACT Feelings of insecurity among adolescents often manifest as self-doubt, social anxiety, and a tendency to evaluate themselves negatively, which can hinder personal development and academic engagement. This condition requires effective intervention strategies within school counseling and guidance services. This study aimed to examine the effectiveness of educational video techniques in reducing the level of insecurity among eighth-grade students at SMPN 11 Mataram in the 2022/2023 academic year. The research employed a quantitative approach with a pre-experimental one-group pretest–posttest design. From a population of 74 students, six students with high levels of insecurity were selected as research participants using purposive sampling. Data were collected using a Likert-scale questionnaire that had been tested for validity and reliability, supported by observations, interviews, and documentation as complementary data. The intervention was conducted through group counseling sessions utilizing educational videos as stimuli for reflection and guided discussion. Data were analyzed using a paired sample t-test at a 5% significance level. The results indicated a significant decrease in insecurity scores after the intervention (t_calculated = 4.952; p < 0.05). These findings suggest that the use of educational videos in group counseling is effective in helping students develop self-acceptance and reduce feelings of insecurity. Therefore, integrating audiovisual media into group counseling services can be recommended as an applicable intervention strategy to support adolescents’ psychological well-being in the school environment. ABSTRAK Perasaan insecure pada remaja sering muncul dalam bentuk keraguan terhadap diri sendiri, kecemasan sosial, serta kecenderungan menilai diri secara negatif yang dapat menghambat perkembangan pribadi dan partisipasi akademik. Kondisi tersebut menuntut adanya strategi intervensi yang efektif dalam layanan bimbingan dan konseling di sekolah. Penelitian ini bertujuan untuk menguji efektivitas penggunaan video edukasi dalam menurunkan tingkat insecure siswa kelas VIII SMPN 11 Mataram Tahun Pelajaran 2022/2023. Penelitian menggunakan pendekatan kuantitatif dengan desain pre-experimental one group pretest–posttest. Dari 74 siswa sebagai populasi, dipilih enam siswa dengan tingkat insecure tinggi melalui teknik purposive sampling. Pengumpulan data dilakukan menggunakan angket skala Likert yang telah diuji validitas dan reliabilitasnya, serta didukung oleh observasi, wawancara, dan dokumentasi sebagai data pelengkap. Intervensi diberikan melalui layanan konseling kelompok dengan pemanfaatan video edukasi sebagai stimulus refleksi dan diskusi terarah. Analisis data menggunakan uji t berpasangan pada taraf signifikansi 5%. Hasil penelitian menunjukkan adanya penurunan skor insecure secara signifikan setelah intervensi diberikan (t_hitung = 4,952; p < 0,05). Temuan ini menunjukkan bahwa penggunaan video edukasi dalam konseling kelompok efektif membantu siswa meningkatkan penerimaan diri dan mengurangi perasaan tidak aman. Oleh karena itu, integrasi media audiovisual dalam layanan konseling kelompok dapat menjadi strategi intervensi yang aplikatif untuk mendukung kesehatan psikologis remaja di lingkungan sekolah.